RESEARCH ON THE QUALITY OF PROCESSING WITH A HORIZONTAL BANDSAW - Atanasov, Valentin; Todorov, Marian; Spasov, Vladimir (Innovation in Woodworking Industry and Engineering design, 2018)
Experimental studies related to the influence of some factors on the quality of the resulting lumber were carried out. The venue of the research is the manufacturing conditions in Experimental and Training Forest Ranges in Barziya. As a work station a horizontal bandsaw for logs Arsov 90 Ltd. (Bulgaria) was used. The results were analyzed and compared to some earlier obtained with other machines of this type. They show that it is not advisable feed speed to exceed 16 m.min-1– due to the risk of unacceptable size deviations. Some recommendations for a more efficient usage of this type machines were proposed.